THE EFFECT OF WORK CLIMATE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE (STUDY ON ONE OF THE 3 STAR HOTELS IN BANDUNG) - Dedi Hadian (Jurnal Computech & Bisnis (e-Journal), 2018)
This research conducted with the aim to determine the effect of work climate and work discipline on employee performance and this study also aims to analyze the most dominant factors of influence between work climate and work discipline on employee performance. The object of his research was that 87 employees used a questionnaire aimed at employees registered at one of the 3-star hotels in the city of Bandung. Based on research using path analysis, it can be seen that the working climate variable (X₁) has a direct influence of 24.1%, indirect influence through relations with work discipline (X₂) of 14.3%, the total effect of 38.4%. Work discipline variables (X₂) have a direct influence of 15.3%, and indirect effects through work motivation (X₁) are 14.3%, the total effect is 29.6%. The results of the correlation coefficient of determination (R squared) expressed in percentages illustrate the contribution of all independent variables namely work motivation (X₁) and work discipline (X₂) in determining the performance variable is 0.679 or 67.9% while other factors that affect performance not examined indicated by the value of 0.321 or 32.1%. The conclusions of the suggestions that can be considered in connection with the results of the study are that management should be able to maintain and improve the two variables above. Keywords: Work Climate, Work Discipline, Employee PerformanceDOI:10.5281/zenodo.3232926